Mesenchymal stem cells and its translation into clinical orthodontics: current trends and future perspectives - Aqeel Ahmed; Hafsa Qabool; Saqib Habib; Mubassar Fida; Syeda Gul Rukh Shah (Journal of the Pakistan Medical Association, 2023)
Oral mesenchymal stem cell populations in humans have been discovered in close vicinity to oral mucosal tissues and both primary (deciduous) and secondary (permanent) teeth. All these different kinds of stem cells have the ability to divide and replenish themselves, however they vary in their gene expression profiles and their capacity to give rise to distinct cell lineages. They all have multipotentiality i.e. chondrogenic, osteogenic, adipogenic, and neurogenic. Due to their relative accessibility, these cell types may form a source of stem cells with substantial potential for application in tissue regeneration. In this review, discoveries outlining stem cell potential are discussed on various aspects as, are their various applications in orthodontics i.e. orthodontic tooth movement, fixing external root resorption, correcting craniofacial anomalies, accelerating craniofacial distraction osteogenesis, recreating the TMJ, and ensuring a stable maxillary expansion. Keywords: Cell, Osteogenesis, Transcriptome, Orthodontics, Stem Cells, Membrane, Temporomandibular